Evaluation of Chemical Composition of Three Potential Fresh Milk Raw Materials From Local Indonesian Regions - Bachri, Syaiful; Sutantio, R. Alamsyah; Hasanah, Niswatin; Karimah, Rinda Nurul; Nurfitriani, Rizki Amalia; Andriyani, Fitriya; Utomo, Budi; Aji, Hutama Puranto (P3M Politeknik Negeri Jember, 2025)
Milk is a nutrient-rich product produced by dairy cattle and plays an important role in preventing stunting in children under five years of age. In the production of milk-based products for toddlers, the quality of raw materials is a critical factor, particularly in terms of standardization and consumer acceptance. East Java Province is one of the largest milk-producing regions in Indonesia, with potential fresh milk sources originating from Jember, Probolinggo, and Banyuwangi Regencies. This study aimed to determine the best fresh milk raw material from these local sources by integrating chemical quality evaluation and hedonic analysis. A quantitative descriptive method was applied using Lactoscan analysis to assess the chemical composition of fresh milk samples. The results showed that all samples met the Indonesian National Standard (SNI) requirements for fresh milk, indicating comparable chemical quality across regions. Although minor variations in nutritional components were observed, these differences were not decisive in determining overall quality. Based on hedonic analysis, fresh milk from Banyuwangi Regency was identified as the most preferred sample. This finding highlights the novelty of the study, demonstrating that when chemical quality among milk samples is relatively similar, sensory preference becomes the determining factor in selecting the best raw material for toddler-oriented milk products.